Model‐based systems engineering for a small‐lift launch facility. Issue 6 (18th July 2022) - Taraila, Walter McGee; Asundi, Sharanabasaweshwara
Abstract: A study of model‐based systems engineering (MBSE) applied to a small‐lift launch facility is presented. The research uses Systems Modeling Language (SysML) products and functional diagrams to document the ground systems on a launch pad servicing a small class payload (0–2 tons). With the projected growth in launch cadence of small‐lift rockets in the coming decade, there is a need to design increasingly complex launch systems with greater efficiency. The potential improvements in project communication, quality, and productivity are explored by developing a model following the ISO/IEC 15288 technical process framework and the International Council on Systems Engineering (INCOSE) Object‐Oriented Systems Engineering Method (OOSEM) methodology. The stakeholder requirements are defined and analyzed to provide traceability to individual systems and subsystems. An architecture is proposed by generating engineering artifacts such as piping and instrumentation drawings. The concepts are verified and validated by performing engineering trade studies concentrated on the pneumatic and fuel subsystems.